Intelligent Fluorescence Probe with Turn‐on Properties By a "See‐Saw" Balance of Visible and Near‐infrared Fluorescence. Issue 12 (19th October 2017) - Jing, Titao; Wu, Ziye; Ruan, Zheng; Li, Tuanwei; Jiang, Jun; Yan, Lifeng
Abstract: Bioimaging requires probes for tracing, especially in the near‐infrared (NIR) region. Herein, A Schiff base dye conjugated with both pyrene and a cyanine (cy7) NIR fluorophores has been synthesized, which showed a novel "see‐saw" fluorescent performance via the combination of aggregation‐induced emission (AIE) and aggregation‐caused quenching (ACQ). The new dye is always switched on in terms of fluorescence by the "see‐saw" balance of the visible and NIR fluorescence. The system is fluorescent in the visible region when it is it is its aggregated state as a result of AIE while it emits NIR fluorescence in the single molecule state. The as‐prepared dye has many potential applications, especially in the field of bioimaging, which was confirmed by in vitro cell experiments. Abstract : A Schiff base dye conjugated with both pyrene and a cyanine (cy7) near‐infrared (NIR) fluorophores has been synthesized, which showed a novel "see‐saw" fluorescent performance through the combination of aggregation‐induced emission (AIE) and aggregation‐caused quenching (ACQ) with the system emitting in both visible and NIR spectral regions.